In-Cell Nanoelectronics: Opening the Door to Intracellular Electrophysiology - Xu, Dongxin; Mo, Jingshan; Xie, Xi; Hu, Ning (Nano-Micro Letters, 2021)
Establishing a reliable electrophysiological recording platform is crucial for cardiology and neuroscience research. Noninvasive and label-free planar multitransistors and multielectrode arrays are conducive to perform the large-scale cellular electrical activity recordings, but the signal attenuation limits these extracellular devices to record subthreshold activities. In recent decade, in-cell nanoelectronics have been rapidly developed to open the door to intracellular electrophysiology. With the unique three-dimensional nanotopography and advanced penetration strategies, high-throughput and high-fidelity action potential like signal recordings is expected to be realized. This review summarizes in-cell nanoelectronics from versatile nano-biointerfaces, penetration strategies, active/passive nanodevices, systematically analyses the applications in electrogenic cells and especially evaluates the influence of nanodevices on the high-quality intracellular electrophysiological signals. Further, the opportunities, challenges and broad prospects of in-cell nanoelectronics are prospected, expecting to promote the development of in-cell electrophysiological platforms to meet the demand of theoretical investigation and clinical application. Highlights: 1 The factors affecting in-cell nanoelectronics for electrophysiology recording were discussed from versatile nano-biointerfaces, penetration strategies, active and passive nanodevices. 2 The applications of in-cell nanodevices in cardiomyocyte and neuron were further reviewed and evaluated. 3 The current challenges of nanodevices for intracellular electrophysiology and their potential applications in biomedical fields were discussed.